Kondo resonances of transition-metal-atom impurities in a metal host: Dependence on d-orbital occupancy. - Goldberg, Edith Catalina (2008)
Kondo resonances for transition-metal-atom impurities in a metal host have been analyzed by means of an ionic model as a function of the impurity d-orbital occupancy. The ionic Hamiltonian has been obtained by making use of the atomic Hund first rule. This Hamiltonian has been solved using a Green-function equation of motion method up to second order in the transition metal–host interaction. We find Kondo temperatures that decrease with the atomic total spin, the largest one appearing for charge fluctuations d0<->d1 and d10<->d9, in good agreement with the experimental evidence.